2015
DOI: 10.1080/09537287.2015.1011725
|View full text |Cite
|
Sign up to set email alerts
|

A hybrid approach to the study of CPFR implementation enablers

Abstract: Abstract:Collaborative planning, forecasting and replenishment (CPFR) is one of the most important, but also one of the most difficult collaborative strategies in supply chain management. CPFR has been well documented in past research as providing significant benefit to those that implement it well. It has also been noted that CPFR take up has been significantly lower than initially expected. The main reason for this slow up take is the general recognition that successful implementation of CPFR is not a trivia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 76 publications
1
25
0
1
Order By: Relevance
“…The experts, who are usually assembled in a small group to build contextual relationships, utilize focus group discussion methods (Shukla, Todorov, and Kapletia 2018). The results of the literature survey revealed that most studies adopting the ISM approach use a small group of experts (ranging from two to 13) from the industry and the academia for developing the contextual relationships (e.g., Chowdhury et al 2020;Haleem et al 2012;Purohit et al 2016;Cherrafi et al 2017;Panahifar, Byrne, and Heavey 2015;Mathiyazhagan et al 2013). Therefore, our team of experts was considered appropriate for this study and adequate for building the proposed ISM model.…”
Section: Data Collectionmentioning
confidence: 99%
“…The experts, who are usually assembled in a small group to build contextual relationships, utilize focus group discussion methods (Shukla, Todorov, and Kapletia 2018). The results of the literature survey revealed that most studies adopting the ISM approach use a small group of experts (ranging from two to 13) from the industry and the academia for developing the contextual relationships (e.g., Chowdhury et al 2020;Haleem et al 2012;Purohit et al 2016;Cherrafi et al 2017;Panahifar, Byrne, and Heavey 2015;Mathiyazhagan et al 2013). Therefore, our team of experts was considered appropriate for this study and adequate for building the proposed ISM model.…”
Section: Data Collectionmentioning
confidence: 99%
“…They indicated that by examining problems and solutions in information security management, standards found that information security management guidelines should be seen as a library of material on information security management for practitioners. A study conducted by Panahifar et al (2015) revealed that information sharing security plays a critical role in collaboration among trading partners. They indicated that firms have to increase information sharing security if they expect both more accurate information and a high level of trust.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the current research, the significant enablers and results of CPFR implementation are selected for further investigation by utilising the system dynamics. Based on the results of previous research, five of the most important enablers and five of the important results are selected to develop a dynamic model in this study [6], [7]. The proposed model is based on a logical assumption that, CPFR implementation will be improved by improving its enablers.…”
Section: Introductionmentioning
confidence: 99%